Efficacy of periodic students’ instructor evaluation to enhance lecturer’s performance: A content analysis - Muchemwa, Stella; Dhiwayo, Alice (S&Co Publishing, 2025)
Systematic collection and analysis of data from students on lecturer’s endeavours in the instruction process is one of the crucial ways of getting feedback on lecturer’s performance. This study underscores the critical aspect of utilizing student feedback as a valuable tool for improving instructional practices and enhancing higher education pedagogical experiences for both educators and students. It focuses on the effectiveness of Periodic Students’ Instructor Evaluation (PSIE) at university level aiming at identifying common themes and areas for improvement. Using the content analysis methodology, the study utilized relevant secondary data sourced from Google web search engine for the period 2018 to 2024. Findings showed that PSIE insights are influential assessment of lecturer’s teaching effectiveness and is an important source of information to the lecturers and the administrators and it enhances quality and programme improvement. Furthermore, PSIE encourages the students’ voice and active participation in university affairs through confidential participation, thereby ensuring that the students’ experiences are fore grounded at the university learning and teaching interface. This meaningful input from students can be critical in the success of such teaching evaluation systems. The researchers also realized that PSIE should be coupled with discussions and consultations of the feedback receivers in order to maximise its utility. Researchers concluded that PSIE is not a witch-hunting exercise but, when properly done, it becomes an important tool with positive impact. This study recommends feedback survey tools that can be tailored to the specific pedagogical approaches and university learning outcomes.